Second premolar extraction: Not always a second choice - Rohan Mascarenhas; Parag Majithia; Shahista Parveen (Contemporary Clinical Dentistry, 2015)
Extraction is a recognized and widely accepted procedure in orthodontic treatment. The selection of teeth for orthodontic extraction is an important decision and they are modified according to the individual patient. This case report describes the management of 18-year old female patient with moderate crowding which was treated with second bicuspid extraction. At the end of treatment, patient had pleasing profile, good intercuspation, ideal overjet, and overbite. The occlusion remained stable even 3 years after orthodontic treatment.